Landauer principle in the context of relativistic communication theory - Alvim, Yuri de Jesus (2023)
This monograph aims to investigate Landauer's principle for a quantum system in a relativistic context. Specifically, we consider a communication channel described by a mode of a quantum field in a curved spacetime. In order to accomplish that, an introduction to Shannon's theorems, as well as some very important concepts in information theory, will be first presented. The relativistic spacetime structure will be described in the sequence, such that the quantum field theory can be used, in this context, to describe the communication channel. Lastly, the calculation of the channel capacity and the energy contributions for the transmission of information over such a channel will be done. Such calculations provide three different contributions to the total energy variation of the system: one due to the change in the spacetime, one associated with the work necessary to switch on or off the interaction between the detectors ---qubits employed to read and codify the information--- with the field and, finally, the last one which is due to the communication process itself. This third contribution vanishes for the considered communication channel, so that no extra energy cost is needed to transmit information once the states of the qubits are settled. The original contribution of this work enters here by considering the cyclical conversion of the transmitted information into work. Since no energy is transferred from the sender to the receiver, this engine apparently violates the second law of thermodynamics. By employing Landauer principle we find the energy contribution which allows the receiver to convert information into work without contradictions with thermodynamics.